Constructing landscapes of value: Capitalist investment for the acquisition of marginal or unused land—The case of Tanzania. (January 2015) - Exner, Andreas; Bartels, Lara E.; Windhaber, Markus; Fritz, Steffen; See, Linda; Politti, Emilio; Hochleithner, Stephan
Highlights: Marginal and unused land refer to two distinct rationalities of domination. They are often employed manipulatively to support biofuel production. In Tanzania, figures on marginal and unused land are poorly supported empirically. In Tanzania, biofuel potentials seem to be very limited, contrary to most views. Abstract: The current global wave of land acquisition – variously debated as land grabbing or investment in land – is promoted by the World Bank and the FAO as creating win–win-situations for local populations and investors alike. Common policy recommendations suggest expanding the production of export crops, by making use of marginal or unused land. Considerable potentials for such an expansion are assumed. Taking Tanzania as a case study, the evidence for such types of land is assessed by using a broad range of statistics. We will argue firstly, that the terms marginal and unused land serve as a manipulative terminology for the benefit of attempts to commercially valorize and commodify African landscapes, from biofuel to large-scale food production and tourism. However, they relate to different rationalities of domination. Unused land refers to a state-bureaucratic narrative, which excludes user groups deemed irrelevant for national development, while marginal land refers to a capitalist-economic narrative that excludes what is not profitable. Secondly, the terms are analyzed as categories central for state simplification of social relations attached to land. Modelling of these land use categories based on remote sensing is an attempt to compensate weak state capacities to enhance the legibility of the landscape by constructing it as a landscape of commercial value.